DAMPAK LIBERALISASI EKONOMI TERHADAP PENGUASAAN TANAH - Herry, Musleh (DE JURE, 2012)
The developmental program of the government creates delicate issues concerning the proper allocation of land. While the government program of welfare necessitates the availability of land to build housings, roads, factories and business centers, the plight of society displaced from their land should not be overlooked. Liberalist approach on managing land proves to bring more problem than solution to the society at large. Through the strong capital and wide network in executive and legislative bodies, the liberalist proponents manage to seize huge amounts of land at the expense of the original owners, mostly villagers who lack of apprehension about the price of land. The vague regulation concerning land also contributes to the handover of huge acres of land from the villagers to the capital owners. Without government intervention on the  land market, it is worried that the process of land acquisition by the capital owner will run out of control.Keywords:  Liberalisasi Ekonomi, Penguasaan Tanah, Hak Milik